Technological properties, in vitro starch digestibility and in vivo glycaemic index of bread containing crude malva nut gum - Phimolsiripol Y. (2017)
© 2017 Institute of Food Science and Technology The effects of crude malva nut gum (CMG) on the texture, digestion and the glycaemic index (GI) of white bread were investigated. Different CMG levels (0%, 2.5%, 5%, 7.5% and 10% w/w based on weight of flour) were added into a bread formula. The lightness (L*) and loaf-specific volumes of the bread decreased with increased CMG levels. Firmness of the bread increased with increased CMG content. The in vitro starch digestion kinetics showed that bread containing CMG had generally lower predicted GI (74–81 vs. the control). In vivo human testing showed that increasing the CMG reduced the GI of the bread. The GI values of bread containing CMG ranged from 73 to 98 of the control. Overall liking scores of consumers ranged between ‘like slightly’ and ‘like moderately’ (6.1–7.1) compared to 7.1 for the control. Thus, the addition of CMG in carbohydrate-based foods may lower the GI.